Challenges to hegemonic masculinity in secondary schools in Mexico City - Torres Hernádez, Jesús (Emerging Trends in Education, 2023)
To understand the functioning of hegemonic masculinity from secondary school, it is necessary to identify the guidelines that validate a way of being a man and inhabiting the school space. Without forgetting the disciplinary nature sanctioning time, activities, personality, bodies. Masculinity is usually understood as a process that produces relational dynamics, legitimizes practices and stories that speak of the experiences of adolescents in secondary schools in Mexico City. The objective of the article is to recover the practices and stories that challenge or question hegemonic masculinity, as well as its forms of management and school intervention. The methodological approach requires identifying the points of conflict, taking as the main source of information the narration or the account of the events in the school context, therefore, focusing on the practices, stories and experiences of sexual orientation, expressions and gender identities. The visibility of other masculinities supposes two transversal axes, present at the moment of interpreting and intervening: heteronormative surveillance as the disposition and forms of school surveillance in the production and legitimacy of male bodies; and the school management of emergencies as the way to intervene in the face of the challenges and tensions that emergent manifestations of masculinity represent.Keywords: hegemonic masculinity, heteronormative surveillance, emergency management, challenges; basic education.